If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 13 = 7e + -21 Reorder the terms: 13 + 5a = 7e + -21 Reorder the terms: 13 + 5a = -21 + 7e Solving 13 + 5a = -21 + 7e Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5a = -21 + -13 + 7e Combine like terms: 13 + -13 = 0 0 + 5a = -21 + -13 + 7e 5a = -21 + -13 + 7e Combine like terms: -21 + -13 = -34 5a = -34 + 7e Divide each side by '5'. a = -6.8 + 1.4e Simplifying a = -6.8 + 1.4e
| 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k | | (-x^2+3x)+(2x^2+7)+(5x-2)= | | 806-?=368 | | z-4=5 | | q+2=3 | | 5x-8x-7= | | 6m+5n-3m+11n= | | 2p^8+5p^4q-12q^2= | | q+.33=.5 | | (5x^2+4x-8)+(3x^2+3x+14)-(8x^2-11)= | | -14y^2-9y^2+12y^2+61xy^2-18xy^2= | | -28-2.6q=-3.8q+4(4.3q+1) | | (3x^2+2x-3)+(5x^2+4x+13)-(8x^2-18)= | | -.7q-(-4+0.9q)=2.8 | | 3.2-9x+7.1-3x=0 | | 7x-1-(x-1)=5x-7 | | (4x+7)-(-2x^2-5x+7)= | | (9x-5)*(9x-5)= | | 7a^3-3a^2+4a+9= | | (-6x+5)+(-4x^2+6x+3)= | | (x-2-3i)(x-2+3i)(x+1)(x-2)=0 | | 2x^225= | | whyunot=work | | 40=110-30t | | 8x+2h=19 | | dropthe=base | | d=110-30t |